Evaluation of the bending properties of profiled skin structure - Al Qaraghuli, Hassan (2016)
A Master of Science thesis in Civil Engineering by Hassan Al Qaraghuli entitled, "Evaluation of the bending properties of profiled skin structure," submitted in January 2016. Thesis advisor is Dr. Adil Tamimi. Soft and hard copy available.